2019
DOI: 10.3390/buildings9010015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Engineering, Procurement and Construction (EPC) Phases on Project Performance: A Case of Large-scale Residential Construction Project

Abstract: The Construction Industry is a complex and fragmented industry worldwide with regards to its supply chain, products, and processes, and is faced with a similar dilemma as faced by manufacturers during its time in past decades. Scope, time, and cost are the triple constraints of project management and leading factors in defining the project performance. Productivity and efficiency of each construction project is measured through its triple constraints, therefore the factors that affect project success are signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 82 publications
1
53
0
1
Order By: Relevance
“…1 = never; 2 = rarely; 3 = sometimes; 4 = often; 5 = very often Table 5 indicates that all the responding construction firms are fully aware of the gap of BPM in the construction industry. As stated by Kabirifar and Mojtahedi (2019), manageable factors such as inadequacy, ineffective control, poor planning, poor allocation, poor design, resources and information, improper implementation and execution, poor dispensation, insufficient quality, and nonmanageable factors such as environmental issues and failure in external methods, are the most significant factors that caused construction project's inefficiency. Evidence has shown that people see construction or building works as a fast way of getting rich, hence, traders, lawyers, microbiologists or political scientists ventures into engineering and building professions undisturbed in the Nigerian construction industry (Osuizugbo, 2018).…”
Section: Data Presentation Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…1 = never; 2 = rarely; 3 = sometimes; 4 = often; 5 = very often Table 5 indicates that all the responding construction firms are fully aware of the gap of BPM in the construction industry. As stated by Kabirifar and Mojtahedi (2019), manageable factors such as inadequacy, ineffective control, poor planning, poor allocation, poor design, resources and information, improper implementation and execution, poor dispensation, insufficient quality, and nonmanageable factors such as environmental issues and failure in external methods, are the most significant factors that caused construction project's inefficiency. Evidence has shown that people see construction or building works as a fast way of getting rich, hence, traders, lawyers, microbiologists or political scientists ventures into engineering and building professions undisturbed in the Nigerian construction industry (Osuizugbo, 2018).…”
Section: Data Presentation Results and Analysismentioning
confidence: 99%
“…Unproductive time such as travelling, waiting, working slowly, doing reworks, and ineffective work are the major causes of productivity loss on construction projects (Aliyu et al, 2015). As stated by Kabirifar and Mojtahedi (2019), manageable factors such as inadequacy, ineffective control, poor planning, poor allocation, poor design, resources and information, improper implementation and execution, poor dispensation, insufficient quality, and nonmanageable factors such as environmental issues and failures in external methods are the most significant factors that caused construction project's inefficiency.…”
Section: Unproductive/ineffective Building Production Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same country, Alao and Jagboro (2017) [22] has reached a decision that delayed payments, fund mismanagement, inadequate budgetary allocation, inadequacy of finance, inflation and bankruptcy of contractor were the most significant causes of abandoned projects. One common reason for abandoned projects is the unpredicted factors causing from the preliminary estimation of the cost of projects through the forecasting stage, the conflicts between the estimated and real construction costs make the project unworkable during the execution stage, such causes may oblige the developer to abandon the project [9].…”
Section: Literature Reviewmentioning
confidence: 99%